More Than Meets the Eye? A Cautionary Tale of Malignant Ectomesenchymoma Treated as Low-risk Orbital Rhabdomyosarcoma. Issue 6 (August 2021) - Rashid, Tooba; Bagatell, Rochelle; Pawel, Bruce; Bentley, Rex C.; Kreissman, Susan G.; Deel, Michael D.
Abstract : Malignant ectomesenchymoma (MEM) is a rare multiphenotypic tumor comprised of mesenchymal and neuroectodermal components. MEM is typically diagnosed in infants and younger children and outcomes are variable. The current approach for treating MEM includes targeting the more aggressive mesenchymal component of the tumor, which is often rhabdomyosarcoma. Here, we describe a case of an orbital tumor initially diagnosed and treated as low-risk rhabdomyosarcoma. Local failure prompting a second biopsy revealed neuronal differentiation consistent with a diagnosis of MEM. Intensifying therapy and local radiotherapy led to a long-term cure. This case offers a cautionary tale that while outcomes for MEM were similar to matched rhabdomyosarcoma cohorts when treated on conventional Intergroup Rhabdomyosarcoma Study Group (IRSG) III/IV protocols, treating MEM using a decreased intensity low-risk rhabdomyosarcoma regimen may not be sufficient.